Geomagnetic Disturbances Due To Neutral‐Wind‐Driven Ionospheric Currents - Cheng Sheng; Yue Deng; Daniel T. Welling; Steven K. Morley (Space Weather)
Abstract Previous simulation efforts on geomagnetic disturbances (GMDs) and geomagnetically induced currents (GICs) mostly rely on global magnetohydrodynamics models, which explicitly calculate the magnetospheric currents and carry certain assumptions about the ionosphere currents. Therefore, the role of ionospheric and thermospheric processes to GMDs has not been fully evaluated. In this study, Global Ionosphere Thermosphere Model simulations for an idealized storm event have been conducted. Simply, the high‐latitude electrodynamic forcing (potential pattern and particle precipitation) has been specified by empirical models. GMDs due to neutral‐wind driven currents have been compared to those caused by magnetospheric convection driven currents during both the main and recovery phases. At locations where the high‐latitude electric potential is dominant, neutral‐wind driven currents are found to contribute to about 10%–30% of the total GMDs. During the recovery phase when the ion‐convection pattern retreats to high latitudes, neutral‐wind driven currents become the primary sources for GMDs at middle latitudes on the dayside due to the “flywheel” effect and the large dayside conductance. Our result strongly suggests that ionospheric and thermospheric processes should not be neglected when estimating GMDs and therefore GICs.